2020
DOI: 10.1088/1757-899x/671/1/012117
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the structural behaviours of self-compacted reinforced concrete hollow beams with in-place circular openings

Abstract: This paper aimed to experimentally investigate the structural conduct of self-compacted concrete hollow beams with various in-place openings. For this purpose, ten reinforced concrete hollow beams were tested under two concentrated and symmetrical loadings. The primary parameter in this study was the location of the openings, and specimens were divided into two groups in addition to the control beam: group one included six beams with openings in front or front and rear of the web, while the second group contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Hassan [33] and Hassan et al [34] experimentally investigated the behaviour of hollow RC beams with different locations of openings subjected to two concentrated loads and indicated that the opening locations highly affected both the ultimate failure loads and stiffnesses. The tested hollow beams possessed reduced stiffnesses and increased deflections.…”
Section: Experimental Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hassan [33] and Hassan et al [34] experimentally investigated the behaviour of hollow RC beams with different locations of openings subjected to two concentrated loads and indicated that the opening locations highly affected both the ultimate failure loads and stiffnesses. The tested hollow beams possessed reduced stiffnesses and increased deflections.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…Many studies have considered various configurations of web openings in RC beams [12][13][14][15][16][17][18][19][20][21][22][23][24][25]. However, other studies have investigated structural behaviours of RC beams with longitudinal openings [8][9][10][11][26][27][28][29][30][31][32][33][34][35][36][37][38][39], and these studies are related to the current study and can be divided into two big groups, i.e., experimental and numerical studies in a chronological order.…”
Section: Introductionmentioning
confidence: 99%
“…There are also many other studies, most of which focus on shallow beams and study the shape, depth, and diameter of the cavities. And the extent of their influence on the shear behavior and flexural behavior of these bundles [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Therefore, there is a lack of studies for hollow deep beams in general, and there is no study in all the literature that investigated the effect of having longitudinal gaps with a slope in all types of RC beams in particular.…”
Section: Introductionmentioning
confidence: 99%
“…Openings in RC members are often provided for reasons like reducing self-weights, electrical supply lines, water and sewerage lines, computer networks, etc., [ 18 , 19 , 20 , 21 ]. Altun et al [ 22 ] tested nine RC beams with dimensions 200 mm × 200 mm × 3000 mm constructed with classic steel fiber reinforced concrete (CSRC).…”
Section: Introductionmentioning
confidence: 99%